Building Smart, Resilient and Sustainable Infrastructure in Developing Countries - MUSONDA, INNOCENT; Mwanaumo, Erastus (Taylor & Francis, 2023)
Building Smart, Resilient and Sustainable Infrastructure in Developing Countries contains the papers presented at the International Conference on Development and Investment in Infrastructure (DII-2022). The contributions cover a wide range of topics related to infrastructure issues on the African continent: Sustainable Infrastructure Development Smart Infrastructure and Cities Quality and Resilient Infrastructure Education, Empowerment, Gender Equity, Wellness and Development Environmental and Waste Management/Facilities & Real-Estate Management Infrastructure, Investment and Finance- Trends and Forecasts Infrastructure: Shock Events, Procurement, Project Management, Health & Safety Infrastructure: Economic, Social/Environmental Sustainability Digital Innovation and transition in the built environment Building Smart, Resilient and Sustainable Infrastructure in Developing Countries evaluates innovations, empowerment, growth and sustainable development of infrastructure development in Africa, and aims at administrators, academics, and professionals.